Substituting in

(A) gives

(B) gives

(C) gives

(A) _{On substituting x = -3 in the given expression, we get}

= (-3)^{2} + 5(-3) + 4 = 9 -15 + 4 = -2

Hence correct expression is:

= (-3)^{2} + 5(-3) + 4 = 9 -15 + 4 = -2

(B)

On substituting x = -3 in the given expression, we get

= (-3)^{2} - 5(-3) + 4 = 9 +15 + 4 = 28

Hence correct expression is:

= (-3)^{2} - 5(-3) + 4 = 9 +15 + 4 = 28

(C) On substituting x = -3 in the given expression, we get

= (-3)^{2} + 5(-3) = 9 -15 = -6

Hence correct expression is:

= (-3)^{2} + 5(-3) = 9 -15 = -6

10